2018
DOI: 10.1007/s00705-018-3950-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of two novel sub-sublineages of pigeon paramyxovirus type 1 in China

Abstract: Pigeon paramyxovirus type 1 (PPMV-1) infection is enzootic in pigeon flocks and poses a potential risk to the poultry industry in China. To gain insight into the biological characteristics and transmission routes of circulating PPMV-1 in pigeons, 13 PPMV-1 isolates from domestic pigeons isolated during 2011-2015 in Guangxi province, China, were characterized using a pathogenicity assessment and phylogenetic analysis. All PPMV-1 isolates were mesogenic or lentogenic strains and had a mean death time (MDT) in 9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Some pigeon farms have extensively been using chicken genotype II vaccines, such as LaSota and Clone-30, in attempts to protect pigeons from ND [13].However, these vaccines have not been fully efficient and the disease has broken in many pigeon farms in China. Previous studies have identified that the predominant viruses causing ND in pigeons in China between 1996 and 2015 were of sub/genotypes VIb (now named VI.1) and VII [14,15]. More recent pigeon-derived PPMV-1 were classified as members of sub-genotypes Vik and VIj [16], which are closely related to the viruses studies here.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Some pigeon farms have extensively been using chicken genotype II vaccines, such as LaSota and Clone-30, in attempts to protect pigeons from ND [13].However, these vaccines have not been fully efficient and the disease has broken in many pigeon farms in China. Previous studies have identified that the predominant viruses causing ND in pigeons in China between 1996 and 2015 were of sub/genotypes VIb (now named VI.1) and VII [14,15]. More recent pigeon-derived PPMV-1 were classified as members of sub-genotypes Vik and VIj [16], which are closely related to the viruses studies here.…”
Section: Introductionsupporting
confidence: 71%
“…PPMV-1 was introduced to Hong Kong in 1985, subsequently spread throughout China, and now poses a serious threat to the Chinese pigeon breeding industry and wild birds population [12]. The virus is now one of the most destructive pathogens for pigeons in the country, also affecting pigeon farms with increased frequency (Awu et al 2015; Guo et al 2013;Ren et al 2016;Wei et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The tree was reconstructed based on the complete F gene (1-1662 nt) sequence using the IQ-TREE software, implemented by the GTR + F + I + G4 model with 1000 bootstrap replicates, using the genotype II NDV strain LaSota as the outgroup.Viruses 2020, 12, 433 6 of 16 Viruses 2020, 12, x FOR PEER REVIEW 6 of Distribution of VI.2.1.1.2.2 pigeon paramyxovirus type 1 (PPMV-1) isolated from China. The Chinese provinces where the presence of VI.2.1.1.2.2 PPMV-1 has been reported are indicated in red.All data were obtained from GenBank in NCBI[37].…”
mentioning
confidence: 99%
“…Distribution of VI.2.1.1.2.2 pigeon paramyxovirus type 1 (PPMV-1) isolated from China. The Chinese provinces where the presence of VI.2.1.1.2.2 PPMV-1 has been reported are indicated in red.All data were obtained from GenBank in NCBI[37].…”
mentioning
confidence: 99%
“…With the rapid development of China's social economy and the continuous improvement in people's quality of life in recent years, the pigeon industry has also developed rapidly, but the epidemic situation of diseases caused by PPMV-1 is not optimistic. Since its first isolation in China in the 1980s, PPMV-1 has long been prevalent in numerous provinces and regions of China, seriously impeding the development of the pigeon industry (23)(24)(25)(26)(27). As a result, it is critical to strengthen the epidemiological surveillance of PPMV-1 in China.…”
Section: Introductionmentioning
confidence: 99%